2006
DOI: 10.1038/ja.2006.67
|View full text |Cite
|
Sign up to set email alerts
|

Tensidols, New Potentiators of Antifungal Miconazole Activity, Produced by Aspergillus niger FKI-2342

Abstract: Two new furopyrrols, designated tensidols A and B, were isolated from the culture broth of Aspergillus niger FKI-2342 by solvent extraction, silica gel column chromatography and HPLC. Their structures were elucidated and shown to have the common skeleton of 6-benzyl-6H-furo [2,3-b]pyrrole. Tensidols A and B potentiated miconazole activity against Candida albicans. Tensidols also showed moderate antimicrobial activity only against Pyricularia oryzae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…7 In this case, a 2008 report by Ding et al unknowingly provided structure 8 9 as a reasonable revision for compound 6 . Our evaluation of both data sets confirmed that the 1 H and 13 C NMR chemical shifts reported for the two compounds were identical and that 8 should be regarded as the correct structure of this metabolite.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…7 In this case, a 2008 report by Ding et al unknowingly provided structure 8 9 as a reasonable revision for compound 6 . Our evaluation of both data sets confirmed that the 1 H and 13 C NMR chemical shifts reported for the two compounds were identical and that 8 should be regarded as the correct structure of this metabolite.…”
Section: Resultsmentioning
confidence: 84%
“…Fortunately, the α -pyridone-containing variant had been previously examined by Ye and colleagues who successfully revised the proposed structure of aspernigrin A ( 3 ) 5 as the more plausible 2-benzylpyridin-4(1 H )-one shown for compound 4 . 8 Our analysis of the furopyrrol-containing molecules, which included tensidols A and B ( 5 - 6 ), 7 led to the observation that these structures had arisen from a strikingly different interpretation of 1 H and 13 C NMR data that were indistinguishable from the values reported for the 2-benzyl-4 H -pyran-4-ones carbonarone A ( 7 ) 6 and pestalamide A ( 8 ), 9 respectively. In this report, we address the structure revision of the tensidols using a combination of NMR spectroscopy, ab initio carbon chemical shift calculations, and total synthesis.…”
mentioning
confidence: 90%
“…However, mixing two or more effective drugs with different mechanisms of action cannot guarantee an improved outcome compared with the results seen with a single agent. BEA was identified before as a potentiator of antifungal miconozole activity in vitro (38,39). Some nonantifungal compounds were also found to enhance the activity of conventional antifungal agents (40).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the new concept of "antiinfective drugs," 5) we have screened microbial metabolites for potentiators of miconazole activity against C. albicans. As a result, we discovered various new compounds: actofunicone, 6) beauvericins, 7) citridones, 8,9) tensidoles 10) and citrinamides 11) from fungi and phenatic acids 12) from an actinomycete. From precise analysis of the metabolites of xanthoradone-producing Penicillium radicum FKI-3765-2, 13) a new compound, designated 6Ј-hydroxy-3Ј-methoxy-mitorubrin (1, Fig.…”
Section: Regular Articlementioning
confidence: 99%